Grafting Techniques for Watermelon - Kent Cushman (EDIS, 2007)
HS-1075, a 5-page illustrated fact sheet by Kent Cushman, provides a brief description of four grafting techniques used for vine crops and a summary of the advantages and disadvantages of each. Includes references. Published by the UF Department of Horticultural Sciences, October 2006.